2014
DOI: 10.1111/1756-185x.12292
|View full text |Cite
|
Sign up to set email alerts
|

99Tc‐methylene diphosphonate improves rheumatoid arthritis disease activity by increasing the frequency of peripheral γδ T cells and CD4+CD25+Foxp3+Tregs

Abstract: Aim: cd T cells exhibit important functions in the pathogenesis of rheumatoid arthritis (RA). In recent years, numerous studies harnessed the cd T cell-activating capacity of aminobiphosphonates for the treatment of malignant tumors. As

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…We also found that the mRNA and protein level of Foxp3 was decreased in the spleens of CIA rats than in normal controls and could be improved by leflunomide both in vivo and in vitro [ 23 ]. These results are consistent with our hypothesis of the involvement of CD4+CD25+Tregs in CIA progression and with the findings of several published studies, which showed an increase of CD4+CD25+Tregs in the therapeutic effect of anti-arthritic drugs on CIA [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the mRNA and protein level of Foxp3 was decreased in the spleens of CIA rats than in normal controls and could be improved by leflunomide both in vivo and in vitro [ 23 ]. These results are consistent with our hypothesis of the involvement of CD4+CD25+Tregs in CIA progression and with the findings of several published studies, which showed an increase of CD4+CD25+Tregs in the therapeutic effect of anti-arthritic drugs on CIA [ 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, among these, there was an increase of Vγ9Vδ2 T cells bearing a terminal effector memory CD27 -CD45RA + phenotype (TEMRA) and a decrease of naïve CD27 + CD45RA + cells [25]. Contrasting with these results, among 19 adults with early active RA, 80% of whom were RF + or anti-cyclic citrullinated peptide (CCP) + and on no current steroid treatment, Vγ9Vδ2 T cells and regulatory T cells (Tregs) were lower, whereas the total percent of γδ T cells was same as in HC [26]. Likewise, among 68 patients with RA (not necessarily designated as early RA), 21 with osteoarthritis (OA) and 21 HC, the percent of γδ T cells in PB was found to be significantly lower in the RA patients, and the percent of Vδ2 + T cells in PB was also decreased in RA relative to OA and HC.…”
Section: Numerical Alterations Of γδ T Cells In Ramentioning
confidence: 91%
“…In this regard, it was further shown that among 19 adults with early active RA, 80% of whom were RF + or CCP + and on no current steroid treatment, treatment with 99Tc-methylene diphosphonate (99Tc-MDP) increased Vγ9δ2 cells and Tregs (which were lower before treatment). Disease activity score (DAS)28, that evaluates disease activity in RA, decreased, as did concentrations of serum TNFα, IL-10, IL-6 during treatment with 99Tc-MDP, whereas IFNγ was unchanged and TGFβ increased [26]. Similarly, among sixty-eight patients with RA, % of Vδ2 T cells in PB correlated inversely with erythrocyte sedimentation rate (ESR), CRP, and DAS28 [27].…”
Section: Relationship To Disease Activity and Severitymentioning
confidence: 98%
“…It has a stable P‐C‐P bond, which targets to bone tissue, inhibits osteolysis caused by tumor, and promotes the role of bone cell proliferation and differentiation . At present, 99 Tc‐MDP has been widely used to treat autoimmune and osteoarthritic diseases, and can also be used to treat osteoporosis and osteopenia . Clinical studies have shown that 99m Tc‐MDP is well concentrated in the jaw ameloblastomas, and OPG, RANKL, and RANK proteins are expressed in the jaw ameloblastoma .…”
Section: Discussionmentioning
confidence: 99%